Bis(-5-hydroxy-2-{[2-(N-phenylthiocarbamoyl)hydrazin-1-ylidene]methyl} phenolato)bis[chloridozinc(II)] N,N-Dimethylformamide tetra-solvate - Tan, Kong Wai; Ng, S.W.; Ng, C.H.; Maah, Mohd Jamil (International Union of Crystallography, 2010)
In the dinuclear title compound, [Zn2(C14H 12N3O2S)2Cl2] ·4C3H7NO, the two monodeprotonated Schiff base ligands N,O,S:Ochelate to Zn atoms. The formally negatively charged O atom involved in chelation also serves as a bridge. The O, O′, N and S atoms comprise a square, and the Cl atom the apex of a square pyramid surrounding each metal atom. The solvate Dimethylformamide molecules, one of which is disordered over two positions in a 3:1 ratio, are hydrogen bonded to the dinuclear molecule. © 2010.